The impact of physics teachers' pedagogical content knowledge and motivation on students' achievement and interest. Issue 5 (29th December 2016) - Keller, Melanie M.; Neumann, Knut; Fischer, Hans E.
Abstract: This paper examines students' achievement and interest and the extent to which they are predicted by teacher knowledge and motivation. Student achievement and interest are both considered desirable outcomes of school instruction. Teacher pedagogical content knowledge has been identified a major predictor of student achievement in previous research, whereas teacher motivation is considered a decisive factor influencing students' interest. So far, however, most research either focused on knowledge or motivation (both on the students' as well as the teachers' side), rarely investigating them together or examining the instructional mechanisms through which the supposed effects of teacher knowledge and motivation are facilitated. In the present study, N  = 77 physics teachers and their classes in Germany and Switzerland are investigated utilizing a multi‐method approach in combining data obtained from test‐instruments (teacher pedagogical content knowledge, student achievement) and questionnaires (teacher motivation, student interest, student perceived enthusiastic teaching) as well as videotaped instruction (cognitive activation rated by observers). Multi‐level structural equation modeling was used to support the assumptions that teacher pedagogical content knowledge positively predicted students' achievement; the effect was mediated by cognitive activation. Teachers' motivation predicted students' interest which was mediated by enthusiastic teaching as perceived by students. Neither did teacher pedagogical content knowledge predict students' interest, nor teacher motivation students' achievement. This implies that in order to improve students' cognitive as well as affective outcomes, both teachers' knowledge but also their motivation need to be considered. © 2016 The Authors. Journal of Research in Science Teaching Published by Wiley Periodicals, Inc. J Res Sci Teach 54:586–614, 2017